α-Lipoic Acid Protects Diabetic Apolipoprotien E-deficient Mice from Nephropathy - Yi, Xianwen (2010)
AIM: Both hyperglycemia and hyperlipidemia increase oxidative stress, and contribute to the development of diabetic nephropathy (DN). We investigated effects of α-lipoic acid, a natural antioxidant and a cofactor in the multienzyme complexes, on the development of DN in diabetic apolipoprotein E-deficient mice. METHODS: Twelve-weeks-old male apoE−/− mice on C57BL/6J genetic background were made diabetic with injections of streptozotocin (STZ). STZ-treated diabetic apoE−/− mice and non-diabetic control were fed with a synthetic high fat (HF) diet with or without LA supplementation. Multiple parameters including plasma glucose, cholesterol, oxidative stress markers, cytokines, and kidney cortex gene expression, and glomerular morphology were evaluated. RESULTS: LA supplementation markedly protected the beta cells and reduced cholesterol levels, attenuated albuminuria and glomerular mesangial expansion in the diabetic mice. Reno-protection by LA was equally effective regardless of whether the dietary supplementation was started 4 weeks before, simultaneously with, or 4 weeks after the induction of diabetes by STZ. LA supplementation significantly improved DN and oxidative stress in the diabetic mice. Severity of albuminuria was positively correlated with level of thiobarbituric acid reactive substances (TBARs) in the kidney (r(2)=0.62, P<0.05). Diabetes significantly changed the kidney expression of Rage, Sod2, Tgfb1 and Ctgf, Pdp2, nephrin and Lias. LA supplementation corrected these changes except that it further suppressed the expression of the Lias gene coding for lipoic acid synthase. CONCLUSIONS: Our data indicate that LA supplementation effectively attenuates the development and progression of DN through its antioxidant effect as well as enhancing glucose oxidation.